Bayesian inference of population expansions in domestic bovines - Finlay, E.K.; Gaillard, C.; Vahidi, S.M.F.; Mirhoseini, S.Z.; Qi, X.B.; El-Barody, M.A.A.; Baird, J.F.; Healy, B.C.; Bradley, D.G.; Han Jianlin (Royal Society, 2007)
The past population dynamics of four domestic and one wild species of bovine were estimated using Bayesian skyline plots, a coalescent Markov chain Monte Carlo method that does not require an assumed parametric model of demographic history. Four domestic species share a recent rapid population expansion not visible in the wild African buffalo (Syncerus caffer). The estimated timings of the expansions are consistent with the archaeological records of domestication.